1997
DOI: 10.1115/1.2815581
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Fuel Cooling Technologies for Advanced Propulsion

Abstract: Storable hydrocarbon fuels that undergo endothermic reaction provide an attractive heat sink for future high-speed aircraft. An investigation was conducted to explore the endothermic potential of practical fuels, with inexpensive and readily available catalysts, under operating conditions simulative of high-speed flight applications. High heat sink capacities and desirable reaction products have been demonstrated for n-heptane and Norpar 12 fuels using zeolite catalysts in coated-tube reactor configurations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(99 citation statements)
references
References 1 publication
0
97
0
2
Order By: Relevance
“…They reported heat sink capacities of 1420-1650 Btu/lbm for JP-7 and 1290-1480 Btu/lbm for JP-8. Sobel and Spadaccini [2] studied catalytic cracking of n-heptane and Norpar 12 fuels over zeolites at temperatures up to 1000 K. These experimental results indicated that catalytic cracking of these fuels provide high cooling rate and excellent product selectivity with excellent combustion characteristics. Fan et al [3] studied the catalytic cracking of China No.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…They reported heat sink capacities of 1420-1650 Btu/lbm for JP-7 and 1290-1480 Btu/lbm for JP-8. Sobel and Spadaccini [2] studied catalytic cracking of n-heptane and Norpar 12 fuels over zeolites at temperatures up to 1000 K. These experimental results indicated that catalytic cracking of these fuels provide high cooling rate and excellent product selectivity with excellent combustion characteristics. Fan et al [3] studied the catalytic cracking of China No.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, several experimental studies have been performed to examine the endothermic properties of aviation fuels with aluminosilicate catalysts under operating conditions simulative of high-speed flight applications (up to 1050 K and 7 MPa) [1][2][3]8,9]. Huang et al [1] performed catalytic cracking of JP-7 and JP-8 using zeolite catalysts at a temperature range of 800-1000 K and measured fuel heat sink, reaction products, and extent of conversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regenerative fuel cooling has been considered one of the most effective and practical methods for hydrocarbonfueled scramjets [1][2][3]. In a regenerative cooling system, before injection into combustor, the fuel flows through the cooling channels along the combustor wall, carrying away heat from the wall via heat convection and endothermic chemical reactions (thermal cracking) [4,5]. A challenge for regenerative cooling systems is that the amount of the fuel used as coolant must match that used for the combustion.…”
Section: Introductionmentioning
confidence: 99%
“…利用燃料在 较高温度条件下的裂解反应, 生成燃烧性能优良的富能 小分子产物, 能为发动机的热管理提供一条有效途径 [2] . 航空燃料组分非常复杂, 包括上百种脂肪烃和芳香 烃化合物, 这些组分的配比对燃料裂解和最终产物产生 重要影响, 因此需要研究各种烃类物质的裂解特性.…”
Section: 引言unclassified